(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The proposed exploration properties analyzes world view. Painting the world is created by human subjective image of objective reality. There are substantial properties worldview and formal properties. Established that the picture of the world carries the basic properties of human vision is credible for its subject and is systemic, imagery, integrity.